Desiccation cracking of heterogeneous clayey soil: Experiments, modeling and simulations. (December 2021) - Hun, Darith-Anthony; Yvonnet, Julien; Guilleminot, Johann; Dadda, Abdelali; Tang, Anh-Minh; Bornert, Michel
Abstract: Experimental results for the cracking of heterogeneous clay samples during desiccation are reported, and an associated numerical model is developed for comparison. The clay samples contain embedded rigid inclusions to induce heterogeneous strain fields during drying. The crack paths and local strain fields are monitored during the desiccation process using digital image correlation. A numerical phase field model for crack initiation and propagation is introduced and compared with the experimental results. A qualitative agreement is found for the obtained crack paths, whereas discrepancies remain for the local strain fields. A discussion regarding the comparison between the experimental results and model is provided. Highlights: Original experimental results of desiccation cracks in heterogeneous clay samples including macro inclusions. Cracks evolution in heterogeneous samples is measured using optical experimental techniques. Strain fields are evaluated experimentally using digital image correlation. A phase field crack model is developed to reproduce the experiments. A comparison and critical discussion on the agreement between experiments and numerical simulations is provided.